Reaction Medium as an Architect of Nanocrystal Superlattices - Seungho Lee; Daniel M. Balazs; Aiswarya Rayaroth; Sharona Horta; Carl P. Goodrich; Michael Engel; Ihor Cherniukh; Maria Ibáñez (Journal of the American Chemical Society, 2026)
Abstract Nanocrystal superlattices are commonly formed by changing concentration, solvent conditions, or particle surface chemistry. Although effective, these approaches alter multiple contributions to the interparticle potential simultaneously, making it difficult to isolate the interactions responsible for ordering or to control assembly in chemically complex environments. Here, we show that oligomeric species present in a nanocrystal reaction medium drive superlattice formation through a depletion mechanism. Using PbTe nanocrystals as a model system, we identify Pb–oleate oligomers in the crude reaction mixture, characterize their solution structure, and quantify their contribution to the interparticle potential, establishing depletion as the dominant short-range interaction governing spontaneous body-centered cubic superlattice formation. We then confirm the depletion origin of ordering by showing that varying depletant concentration predictably shifts the order–disorder boundary and produces a thermally reversible transition between dispersed and ordered states ─ behavior that is inconsistent with van der Waals or ligand-mediated mechanisms but is a direct consequence of depletion control. Having established and validated the mechanism, we demonstrate that the same depletion framework can be deliberately activated in purified dispersions and transferred across nanocrystal systems of different composition and shape, including anisotropic and binary assemblies. These results establish precursor-derived depletion as a general and chemically grounded mechanism for nanocrystal superlattice formation, and show that collective ordering can be programmed through the surrounding medium rather than through particle surface modification.